The importance of dermatological lesions in the agile diagnosis of Monkeypox - Dominguez Alvarado, Gonzalo; Arboleda Roca , Angie Marcela; Bolívar Cabrera , Aymer Daniel; Curicó Martínez, Gabrielle Yolmari; Millán Guerrero , Laura Camila (Journal of Pakistan Association of Dermatologists, 2022)
NA